Influence of the Fabrication Accuracy of Hot-Embossed PCL Scaffolds on Cell Growths - Limongi, Tania; Dattola, Elisabetta; Botta, Cirino; Coluccio, Maria Laura; Candeloro, Patrizio; Cucè, Maria; Scopacasa, Bernadette; Gallo Cantafio, Maria Eugenia; Critello, Costantino Davide; Pullano, Salvatore Andrea; Fiorillo, Antonino S.; Tagliaferri, Pierosandro; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Polycaprolactone (PCL) is a biocompatible and biodegradable polymer widely used for the realization of 3D scaffold for tissue engineering applications. The hot embossing technique (HE) allows the obtainment of PCL scaffolds with a regular array of micro pillars on their surface. The main drawback affecting this kind of micro fabrication process is that such structural superficial details can be damaged when detaching the replica from the mold. Therefore, the present study has focused on the optimization of the HE processes through the development of an analytical model for the prediction of the demolding force as a function of temperature. This model allowed calculating the minimum demolding force to obtain regular micropillars without defects. We demonstrated that the results obtained by the analytical model agree with the experimental data. To address the importance of controlling accurately the fabricated microstructures, we seeded on the PCL scaffolds human stromal cell line (HS-5) and monocytic leukemia cell line (THP-1) to evaluate how the presence of regular or deformed pillars affect cells viability. In vitro viability results, scanning electron and fluorescence microscope imaging analysis show that the HS-5 preferentially grows on regular microstructured surfaces, while the THP-1 on irregular microstructured ones.